PENGARUH KUALITAS AUDIT, LIKUDITAS, KONDISI KEUANGAN PERUSAHAAN, UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP PENGUNGKAPAN GOING CONCERN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2011-2013 - Syafriliani -; Zulbahridar -; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed at examining the effect of audit quality, the financial condition, size, growth, and the previous year's audit opinion on audit going concern disclosure. The population of this study are manufature companies listed on the Indonesian Stock Exchange (BEI), from 2011 to 2013. The samples of the study are all companies were selected by purposive sampling method. Based on the criteria, 40 companies were chosen as the samples of this study. Data analysis usied Logistic models (logit). The study states that the company's financial condition and the previous year's audit opinion had a significant influence on the auidt going concern opinion on manufacturing companies during the period 2009 to 2011. While the quality of public audit, company size and growth do not significantly influence the audit going concern opinion. Value of determination coefficient of 0.432, which means that the variability of the dependent variable can be explained by the independent variable as 43.20%, while the remaining variables 56.80% is explained by the variability of other variables outside the model study.Keywords: Quality, Financial, Size, Growth and Audit